Kathe Kollwitz Kekelaman Dan Kepedihan Dalam Karya Seni Cetak Grafisnya - Mahendrapati, Nawangseto (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2012)
Ekspressionis artist Kathe Kollwitz was a woman from Germany who has a major reputation as a graphic artist, althought he began his career as a painter and ended by making sculptures. His works done by combining technical masteryof the powerful, often shocking and disturbing, images were shown to the whole message strong. The overall theme of his work is mainly social and political, but the quality of emotional expression that is not chaotic. Kolwitz Kathe works that use black and white and the use of lighting effects felt very tense and dramatics. Facial expression and position objects depicted actually can represent feelings.This article discusses the background of the creation of works of graphic art prints by Kathe Kollwitz aesthetic approach. What factors underlying the creation of works of Kathe Kollwitz dark and gripping, and whether the expression of fellings like Kathe Kollwitz poured through his work with graphic print art techniques.Keywords : printmaking, dramatically, Kathe Kollwitz, Therapy